Exchange Rate Elasticities of International Tourism and the Role of Dominant Currency Pricing - Ding Ding; Yannick Timmer (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate exchange rate elasticities of international tourism. We show that, in addition to the bilateral exchange rate, the exchange rate between the tourism origin country vis-à-vis the U.S. dollar is an important driver of tourism flows, indicating a strong role of U.S. dollar pricing. The U.S. dollar exchange rate is more important for tourism destination countries with higher U.S. dollar borrowing, pointing toward a complementarity between U.S. dollar pricing and financing. Country-specific dominant currencies (CSDCs) play only a minor role for the average country but are important for tourism-dependent countries and those with a high concentration of tourists. The importance of the U.S. dollar exchange rate represents a strong piece of evidence of dominant currency pricing (DCP) in the international trade of services and suggests that the benefits of exchange rate flexibility for tourism-dependent countries may be weaker than previously thought.
Keywords: 330; exchange rates; trade; tourism; dominant currency pricing